Breast cancer metastases to the stomach with endoscopic submucosal dissection: a case report and literature study - Zhao, Qingmiao; Dou, Lizhou; Feng, Xiaolong; Wang, Guiqi; He, Shun (Frontiers in Oncology, 2025)
Breast cancer (BC) is the second leading cause of cancer-related death in women, with mortality primarily associated with metastasis. Although gastric metastasis is rare, there are still case reports in the literature. Clinical symptoms of gastric metastasis from BC are often nonspecific, and endoscopic presentations are heterogeneous. Distinguishing between primary and metastatic tumors is important and challenging for the endoscopist. Herein, we report a case of gastric metastasis occurring 4 years after BC surgery. The timeline is as follows. In 2019, the 60-year-old woman received neoadjuvant chemotherapy followed by left breast radical surgery and endocrine therapy with targeted treatment. In 2022 (3 years post-surgery), left axillary metastasis was diagnosed, requiring excision of a skin mass. In 2023 (4 years post-surgery), she presented with upper abdominal pain and acid reflux, and gastroscopy revealed a superficial flat lesion in the gastric antrum. Immunohistochemical (IHC) staining suggested the possibility of poorly differentiated adenocarcinoma. Contrast-enhanced computed tomography (CT) revealed focal abnormal enhancement of the gastric antrum without evidence of distant metastasis. Since endoscopic, imaging, and IHC staining findings did not clearly suggest BC metastasis, and considering the patient’s history of BC and overall condition, she underwent endoscopic submucosal dissection (ESD)-a procedure performed with both diagnostic and therapeutic intent. The postoperative pathology revealed metastatic invasive lobular carcinoma (ILC) of the breast. The ESD not only clarified the patients’ diagnosis but also avoided unnecessary surgery for the patient. The patient remains alive under maintenance therapy. In summary, our case highlights the role of ESD, which was performed with both diagnostic and therapeutic intent—in managing gastric metastasis from BC, while underscoring the necessity of regular endoscopic surveillance post-mastectomy.